FHOD1 is a combined actin filament capping and bundling factor that selectively associates with actin arcs and stress fibers - Schönichen, André; Mannherz, Hans Georg; Behrmann, Elmar; Mazur, Antonina J.; Kühn, Sonja; Silván, Unai; Schoenenberger, Cora-Ann; Fackler, Oliver Till; Raunser, Stefan; Dehmelt, Leif; Geyer, Matthias (Journal of cell science, 2013)
Formins are actin polymerization factors that are known to nucleate and elongate actin filaments at the barbed end. In the present study we show that human FHOD1 lacks actin nucleation and elongation capacity, but acts as an actin bundling factor with capping activity toward the filament barbed end. Constitutively active FHOD1 associates with actin filaments in filopodia and lamellipodia at the leading edge, where it moves with the actin retrograde flow. At the base of lamellipodia, FHOD1 is enriched in nascent, bundled actin arcs as well as in more mature stress fibers. This function requires actin-binding domains located N-terminally to the canonical FH1-FH2 element. The bundling phenotype is maintained in the presence of tropomyosin, confirmed by electron microscopy showing assembly of 5 to 10 actin filaments into parallel, closely spaced filament bundles. Taken together, our data suggest a model in which FHOD1 stabilizes actin filaments by protecting barbed ends from depolymerization with its dimeric FH2 domain, whereas the region N-terminal to the FH1 domain mediates F-actin bundling by simultaneously binding to the sides of adjacent F-actin filaments.
Gesehen am 15.07.2021
DOI funktioniert nicht